The Fifth Interlinguistics Symposium of the Interlinguistic Studies of Adam Mickiewicz University in Poznań - Koutny, Ilona; Stria, Ida; Farris, Michael (Investigationes Linguisticae, 2020)
The Fifth Interlinguistics Symposium of the Interlinguistic Studies of Adam Mickiewicz University in Poznań